Understanding women's motivations to participate in MTN-003/VOICE, a phase 2b HIV prevention trial with low adherence - Ariana W. K. Katz; Barbara S. Mensch; Kubashni Woeber; Petina Musara; Juliane Etima; Ariane van der Straten (BMC, 2019)
Abstract Background In biomedical prevention trials, correct and consistent use of the investigational product is crucial to determine efficacy. Product adherence in VOICE, a phase 2B randomized trial of a vaginal gel and oral tablets for HIV prevention, was low (~ 34%), yet self-reported adherence and retention was high (> 90%). This analysis from VOICE-D, a post-trial qualitative ancillary study, explores motivations to participate in VOICE, and possible sources of misalignment between the stated priorities of the trial and the participants. Methods VOICE-D enrolled 171 former VOICE participants to investigate, among other things, reasons for joining and remaining in the trial. Local language in-depth interviews and focus groups were transcribed and translated into English and coded and analyzed using NVivo. Data on motivation to join obtained from a VOICE termination visit survey of 106 participants were also analyzed to corroborate the VOICE-D findings. Results Participants primarily participated for personal health benefits (e.g. free healthcare and HIV testing) and reported remaining enrolled from a sense of commitment to the trial. Altruistic motivations were the most commonly stated motivation on the termination visit survey; qualitatively, many of those stating altruistic reasons also desired personal health benefits. Joining for financial reimbursement was not commonly mentioned. Social networks influenced recruitment and spread therapeutic misconception. Conclusions Women's participation for personal health benefits highlighted their desire to monitor their HIV risk and overall health. Helping participants view use of investigational products as improving social capital and reminding participants of their study responsibilities may improve trial outcomes. Understanding the reasons for participating in studies will help to ensure alignment between priorities of researchers and participants. Trial registration NCT02358616; Posted February 9, 2015, retrospectively registered.